Academic Suffocation: Students and Efforts to Build Inner Balance - Annisa Addini Tanjung; Hotnita Putri Siregar; Nur Jelita Gultom; Awaliyah Putri (Madiha Press, 2026)
Academic pressure experienced by students often negatively impacts their psychological condition and inner balance. The background of this study lies in the increasin cases of mental exhaustion, anxiety, and emotional instability resulting from high academic demands, peer competition, and the lack of adequate emotional support systems. This research aims to identify the forms of academic pressure perceived by students, as well as the strategies they use to build and maintain inner balance amid such stress. The research method used is a descriptive qualitative approach, with data collection techniques in the form of in-depth interviews involving 15 students from various study programs at both public and private universities in Indonesia. The data were analyzed using thematic methods to reveal common patterns in the students' experiences and strategies. The research findings indicate that students face pressure arising from overwhelming assignments, high academic expectations, and social pressures from their surroundings. In response, students develop various efforts to build inner balance, including spiritual practices (such as meditation and prayer), better time management, recreational activities, and seeking emotional support from peers or campus counselors. The conclusion of this study shows that efforts to build inner balance are dynamic processes that are strongly influenced by self-awareness and environmental support. Interventions from the university, such as the provision of counseling services and stress management programs, are crucial to help students cope with academic pressure in a healthier and more constructive manner.